Pendampingan Pengelolaan dan Pengolahan Pasca Panen Kopi Secara Berkelanjutan di Desa Curahpoh Bondowoso - Setiyono; Arum, Ayu Puspita; Patricia SM, Susan Barbara; Savitri, Dyah Ayu; Anggraini, Febri; Maulana, Juraisyki Iqbal (Universitas Mataram, 2024)
Curahpoh Village is an important part of the Bondowoso Coffee Republic. Curahpoh Village coffee farmers who are members of LMDH Argo Santoso cultivate Robusta Coffee and Arabica Coffee. However, the limited resources owned by farmers mean that coffee farming in Curahpoh Village has not received optimal results. The quality of the coffee products produced is also not supported by appropriate processing technology. Farmers usually only process coffee dry (natural process) because it is simpler. Processed coffee is also generally harvested and not sorted properly. Efforts to increase agricultural productivity are efforts that must be carried out in an integrated manner from upstream to downstream and sustainably. This community service program aims to increase the willingness and skills of farmers in managing coffee farming, especially related to post-harvest. The community service program educated LMDH Argo Santoso farmers to sort the fruit so that the coffee cherries that will be processed are coffee that is at least 95% ripe and has no defects. The coffee cherries that have been sorted are then directed to be processed using the honey method. Sensory evaluation of natural and various honey-processed coffee showed that about 90% of the farmers prefer honey method to natural method. Farmers are also trained to make organic fertilizer from dried coffee husks that are abundance in Curahpoh village. Hopefully, this service program will stimulate the farmers to implement good practices of coffee sorting, processing methods, and waste management.